Multicultural Fiqh Instruction to Improve Religious Tolerance and Moderation Among Pesantren Students - Rusydiyah, Evi Fatimatur; Jazil, Saiful; Zahro, Ahmad (Didaktika Religia, 2023)
This article examines the introduction of special Fiqh textbooks in religious schools to increase religious tolerance and curb religious extremism among the students. This research selected 29 of 179 articles based on inclusion and exclusion criteria such as period, document type, and source. PRISMA was used as a guide for article selection in this study and Lens.org, Eric, and Garuda as literature search databases. The results of research through SLR showed that Fiqh learning methods with innovative approaches can lead to improved learning achievements for students. Fiqh instruction focusing on multicultural communities can foster more tolerant and moderate attitudes among students who learn to respect religious differences, widen their intellectual horizons, be more critical of their own views, and are willing to enter into a constructive dialogue with other communities. This approach can improve their ability to find solutions to multidimensional problems. This integral-holistic method also supports academic, spiritual, emotional, social, and creative aspects of learning how to interact in a multicultural environment .